Efficacy of Reminiscence Therapy on Cognitive Functioning in Older Adults: A Horticultural Life Review Program. Issue 2 (April 2018) - Lin, Li-Jung; Yen, Hsin-Yen
Abstract : Both life review programs and horticulture are beneficial for older adults' cognitive functioning. The purpose of this study was to examine the cognitive effects of reminiscence therapy. Participants older than 65 years in a day care center were recruited, and 14 of 24 participants were assigned to an experimental group. The intervention was based on Erickson's life stages and using plant lives as a metaphor for a human's life from birth to death. The intervention program was designed for 7 weeks of seven 1-hour sessions. The results demonstrated that the subscale scores of Orientation and Memory in the experimental group improved significantly. Total scores of the Loewenstein Occupational Therapy Cognitive Assessment were significantly improved in the experimental group following the intervention. Reminiscence therapy has cognitive benefits for older adults. The Horticultural Life Review Program is recommended for promoting older adults' psychological health.